COMPARATIVE ANALYSIS OF THE ARABIC AND ROMANIAN PHONETIC SYSTEMS: A CONTRASTIVE GRAMMAR APPROACH - Yousra Rouchdi (Studii de gramatică contrastivă)
This paper presents an ongoing study that examines the phonetic systems of Arabic and Romanian using a contrastive grammar approach, which is a branch of applied linguistics that compares the grammatical structures of two languages. The focus of the research is on auditory phonetics, particularly how the phonetic differences between Arabic and Romanian affect the learning process for speakers of Romanian who are acquiring Arabic as a second language. This study employs a qualitative case study method, involving Romanian learners of Arabic who have no prior exposure to the language. The objective is to assess their perceptual challenges in distinguishing Arabic phonemes, which are often quite distinct from those in Romanian. By analysing the specific phonetic obstacles faced by these learners, the research aims to provide insights into the unique difficulties associated with learning Arabic phonetics for Romanian speakers. The findings reveal that Romanian learners struggle with certain Arabic phonemes that do not have direct equivalents in Romanian, such as emphatic consonants and sounds produced in the pharyngeal and uvular regions of the vocal tract. These difficulties are attributed to the lack of similar sounds in Romanian, leading to challenges in both perception and production of Arabic phonemes. This study’s implications are significant for language pedagogy, suggesting that targeted phonetic training and increased exposure to the unique sounds of Arabic can help mitigate these perceptual challenges. Ultimately, this research contributed to a deeper understanding of the phonetic hurdles in learning Arabic as a second language.